A Novel Spore Wall Protein from Antonospora locustae (Microsporidia: Nosematidae) Contributes to Sporulation. (10th April 2017) - Chen, Longxin; Li, Runting; You, Yinwei; Zhang, Kun; Zhang, Long
Abstract: Microsporidia are obligate intracellular parasites, existing in a wide variety of animal hosts. Here, we reported Aloc SWP2, a novel protein identified from the spore wall of Antonospora locustae (formerly, Nosema locustae, and synonym, Paranosema locustae ), containing four cysteines that are conserved among the homologues of several Microspodian pathogens in insects and mammals. Aloc SWP2 was detected in the wall of mature spores via indirect immunofluorescence assay. In addition, immunocytochemistry localization experiments showed that the protein was observed in the wall of sporoblasts, sporonts, and meronts during sporulation within the host body, also in the wall of mature spores. AlocSWP2 was not detected in the fat body of infected locust until the 9th day after inoculating spores via RT‐PCR experiments. Furthermore, the survival percentage of infected locusts injected with dsRNA of AlocSWP 2 on the 15th, 16th, and 17th days after inoculation with microsporidian were significantly higher than those of infected locusts without dsRNA treatment. Conversely, the amount of spores in locusts infected with A. locustae after treated with RNAi AlocSWP2 was significantly lower than those of infected locusts without RNAi of this gene. This novel spore wall protein from A. locustae may be involved in sporulation, thus contributing to host mortality.